ANALISIS INVESTASI ASING LANGSUNG (FDI) DI NEGARA ASEAN TAHUN 2000-2017 - Futuhatul Barorah; Nazaruddin Malik; Zainal Arifin (Jurnal Ilmu Ekonomi JIE, 2019)
The aim of this research is nalyze foreign direct investment (FDI) from 2000 to 2017. The analytical tool used was multiple linear regression with panel data method by testing hypotheses namely F test, t-test, and Determination Coefficient R2. The software used in the analysis of this study was Eviews 9. The finding of the study denotes that all of influence of GDP growth, Trade Openness, Interest Rate and Inflation gave influence toward on Foreign Direct Invesment with a probability value of 0,0000. While individually, The country of Myanmar has the highest intercept inversely proportional to Malaysia which has the smallest intercept. While individually GDP growth and Trade Openness has a positive and significant effect on Foreugn Direct Invesment, Interest Rate and inflation has a negative and significant effect on Forign Direct Invesment.